IDENTIFIKASI KEJADIAN GASTRITIS PADA SISWA SMU MUHAMMADYAH 3 MASARAN - Eka Novitayanti (Universitas Duta Bangsa Surakarta, 2020)
Gastritis is a digestive problem that often occurs in adolescents, mostly attacking students and students. Gastritis is inflammation of the gastric mucosa. This study aims to determine the incidence of gastricitis in Muhammadyah 3 Masaran High School. The research method used was descriptive observational research. The population in the study were all students of Muhammadyah 3 Masaran High School. The sample research technique is total sampling where all members of the population are sampled. Results Identification of the incidence of gastritis in Muhammadyah High School 3 Masaran of 52 respondents who experienced gastritis as many as 27 respondents (51.9%). Gastritis is suffered a lot by high school students who are classified as teenagers because of irregular eating, so that it will disrupt the daily activities of high school students. Conclusion most of Muhammadyah 3 High School students in Masaran have gastritis. This research suggests students increasingly know the incidence of gastritis, causes and signs of symptoms so as to avoid the causes of gastritis.